Bacteriophages in sewage: abundance, roles, and applications. (17th March 2022) - Ballesté, Elisenda; Blanch, Anicet R; Muniesa, Maite; García-Aljaro, Cristina; Rodríguez-Rubio, Lorena; Martín-Díaz, Julia; Pascual-Benito, Miriam; Jofre, J
ABSTRACT: The raw sewage that flows through sewage systems contains a complex microbial community whose main source is the human gut microbiome, with bacteriophages being as abundant as bacteria or even more so. Phages that infect common strains of the human gut bacteriome and transient bacterial pathogens have been isolated in raw sewage, as have other phages corresponding to non-sewage inputs. Although human gut phages do not seem to replicate during their transit through the sewers, they predominate at the entrance of wastewater treatment plants, inside which the dominant populations of bacteria and phages undergo a swift change. The sheer abundance of phages in the sewage virome prompts several questions, some of which are addressed in this review. There is growing concern about their potential role in the horizontal transfer of genes, including those related with bacterial pathogenicity and antibiotic resistance. On the other hand, some phages that infect human gut bacteria are being used as indicators of fecal/viral water pollution and as source tracking markers and have been introduced in water quality legislation. Other potential applications of enteric phages to control bacterial pathogens in sewage or undesirable bacteria that impede the efficacy of wastewater treatments, including biofilm formation on membranes, are still being researched. Abstract : This paper reviews the abundance, roles, and applications of bacteriophages from sewage.